The assessment of the body temperature of critically ill patients in intensive care: from evidence to clinical practice - Dias Paulo Ferreira de Sousa, Diana Julia (2025)
Introduction: The assessment of body temperature requires that care professionals, in their decision-making, determine the method of assessment with scientific and technical rigor. Therefore, the goals of this study are to determine the reliability of five methods for assessing body temperature in critically ill patients and determine the accuracy of four non-invasive temperature assessment methods compared to the esophageal method. Materials and Methods: Quantitative, descriptive-correlational study, developed in an intensive medicine unit of a Portuguese hospital, with 65 assessments, on a sample of 30 hospitalized patients. Five methods of assessing body temperature were used. Results: There are significant differences in the variation in body temperature between the five methods, particularly in the values obtained by the tympanic and axillary thermometers whem compared with the esophageal thermometer, but without statistical differences when comparing the average esophageal temperatures  with the average temperatures in frontal region and the groin skin. Discussion: The esophageal thermometer is accurate and reliable, assessing the core temperature, continuously, which corresponds to what in described in the literature. Peripheral temperature thermometers proved to be less accurate and reliable than the esophageal thermometer. However, the results of using the frontal thermometer and the skin thermometer demonstrares that they are at an advantage over the other methods, when compared with the esophageal one. Conclusion: The evaluations obtained show differences among the methods. However, it is important to understand these diferences in a larger sample and whether there are other factors that may influence the results.